Ethnobotanical study of wound healing plants in Kpando Traditional Area, ghana. - Victor Y. A Barku; Yaw Opoku-Boahen; Gertrude A Dali (International Journal of Phytomedicine, 2014)
Background: An ethnobotanical survey was undertaken in the Kpando Traditional Area of Volta Region in Ghana to identify and record information on medicinal plants used for treating wounds. Methods: Traditional Medical Practitioners (TMP’s) and inhabitants both young and adults were interviewed using semi-structured questionnaires and open-ended conversations. Field trips were made to the sites where TMP’s harvest plants. Results: The survey identified and recorded 27 plants species from 20 families, used for treating wounds in Kpando. The Euphorbiaceae (30.0 %) was the most represented plant family while herbs made up 57.0 % of the total medicinal plants used. Ten plant species namely; Adiatum veneris capillus L. (Rutaceae), Vernonia colorata (Willd.) Drake (asteraceae/compositae), Combretum dolichopetalum Engl. & Diels (Combretaceae), Coffee arabica (Rubiaceae), Milicia excelsia (Welw.) C. C. Berg. (Moraceae), Anogeissus leiocarpus (DC) Guill and Perr. (Combretaceae), Spondias mombin L. (Anacardiaceae), Bridelia ferruginea Benth. (Euphorbiaceae), Amaranthus spinosus Linn. (Amaranthaceae) and Corchorus olitorius L. (Tiliaceae) have not previously been documented for the treatment of wound in Ghana. The leaf was the most commonly used plant part while grinding the fresh part of plant to form poultice was the most common method of traditional drug preparation. Almost all the medicinal plants (95%) are harvested from immediate surroundings. Knowledge of the use of plants as medicines does not only remain with the older generation but extends to the youth who show much interest. Majority still depends on the use of plants for wound healing as the first choice of medication. Conclusions: Different number of plants species are used for treating wound among the people of Kpando Traditional Area. Several traditional uses of these plants still need to be explored by both in vitro and in vivo bioassays leading to further investigations for the identification of their chemical compounds of therapeutic value